PODCAST ON DEVELOPING LISTENING COMPREHENSION OF EFL LEARNERS - Lalu Achmad Noviyandi; Kholid Kholid; Syairal Fahmy Dalimunthe (Universitas Negeri Medan, 2022)
ABSTRACTPodcast on developing listening comprehension of EFL Learners (An Experimental Study at the eleventh students of SMAN 1 Sikur in the school years of 2013/2014?This research is aimed at finding out whether: (1) Podcast is more effective than conventional technique to teach listening skill at the eleventh students of SMAN 1 Sikur in the school years of 2013/2014, (2) In what way does the effect of podcast influence listening comprehension of EFL learners for the eleventh students of SMAN 1 Sikur in the school years of 2013/2014?The method which was applied in this research was experimental study. It was conducted at the eleventh students of SMAN 1 Sikur in the school years of 2013/2014. The population of the research is the IX.A Grade Students of eleventh students of SMAN 1 Sikur in the school years of 2013/2014 . The sample was 1 class. In taking the sample, a cluster random sampling technique was used. Each class was divided into two groups (Experimental and control groups). Then, the techniques which were used to collect the data were an intelligence test for getting the data of the students’ intelligence and a multiple choice test for getting the data of the students’ listening comprehension. The instruments were tried out to get valid and reliable items. The data were analyzed by using multifactor analysis of ANOVA 2x2 and tukey test.Based on the findings, it can be concluded that in general podcast technique is more effective than conventional technique to teach listening. For the students who have high or low intelligence, podcast technique is more effective than conventional technique to teach listening.In accordance with the above result, the English teacher is expected to be able to select the appropriate teaching technique to teach vocabulary for the students who have high or low intelligence.Key words: Podcast, conventional Technique, Listening